Stem cells and heart: an open future or a mirage? - Pier Paolo Bassareo; Giuseppe Mercuro (Hygeia Press di Corridori Marinella, 2016)
Stem cells (SC) look like to be the possible solution to a number of human pathologies, including those involving the heart. In fact, some studies based on animal models suggest that SC can be used to repair the damaged cardiac tissue, such as in case of myocardial infarction. In fact it has been demonstrated that it would be possible to produce a quantity of SC sufficient to repair an animal heart having physiology and dimensions as the human heart. The aim of this short review is to examine the different subtypes of SC potentially involved in the heart repair (autologous and heterologous) processes as well as the serious concerns that have still to be overcome before considering SC a sure therapy for the heart diseases: rejections, oncogenesis due to SC high proliferative activity, difficult in ruling their differentiation, massive SC death when introducing them in an ischemic environment, ethical problems when SC are derived from embryos.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano